Surface modification of pig endothelial cells with a branched heparin conjugate improves their compatibility with human blood - Anjan K. Bongoni (Nature Portfolio, 2017)
Abstract Corline Heparin Conjugate (CHC), a compound of multiple unfractionated heparin chains, coats cells with a glycocalyx-like layer and may inhibit (xeno)transplant-associated activation of the plasma cascade systems. Here, we investigated the use of CHC to protect WT and genetically modified (GTKO.hCD46.hTBM) pig aortic endothelial cells (PAEC) in two pig-to-human in vitro xenotransplantation settings. Model 1: incubation of untreated or hTNFα-treated PAEC with 10% human plasma induced complement C3b/c and C5b-9 deposition, cellular activation and coagulation activation in WT and GTKO.hCD46.hTBM PAEC. Coating of untreated or hTNFα-treated PAEC with CHC (100 µg/ml) protected against human plasma-induced endothelial activation and damage. Model 2: PAEC were grown on microcarrier beads, coated with CHC, and incubated with non-anticoagulated whole human blood. Genetically modified PAEC significantly prolonged clotting time of human blood (115.0 ± 16.1 min, p < 0.001) compared to WT PAEC (34.0 ± 8.2 min). Surface CHC significantly improved the human blood compatibility of PAEC, as shown by increased clotting time (WT: 84.3 ± 11.3 min, p < 0.001; GTKO.hCD46.hTBM: 146.2 ± 20.4 min, p < 0.05) and reduced platelet adhesion, complement activation, coagulation activation and inhibition of fibrinolysis. The combination of CHC coating and genetic modification provided the greatest compatibility with human blood, suggesting that pre-transplant perfusion of genetically modified porcine organs with CHC may benefit post-transplant xenograft function.